Integrated metabolomic and transcriptomic analysis highlight the flavonoid response to antioxidant activity and Aspergillus flavus resistance in peanut seed coats - Xuejie Zhao; Minghui Xing; LiJing Zhang; Suoyi Han; Xinyou Zhang; Jinyong Huang (BMC Plant Biology)
Abstract Background Peanut seeds exhibit a high susceptibility to infection by Aspergillus flavus (A. flavus) post-harvest, which significantly limits their storage and marketability. The peanut seed coat acts as a crucial barrier against A. flavus, containing abundant flavonoids. Despite ongoing research, a comprehensive understanding of the inhibitory effects of flavonoids present in peanut seed coats on A. flavus remains elusive. Results This study reveals significant differences in antioxidant activities and resistance to A. flavus among seed coat extracts from different peanut cultivars. A total of 1,314 metabolites were identified through untargeted metabolomics, among which flavonoids enhance both antioxidant activity and pigmentation in the seed coat. Compounds such as anthocyanins, aurones, and chalcones were strongly associated with increased resistance to A. flavus. Notably, cyanidin-3-O-sophoroside exhibited the highest concentration (10.83 mg/g dry weight) and demonstrated a minimum inhibitory concentration (MIC) of 50 µg/mL. By integrating transcriptomic and metabolomic data, we revealed candidate genes and metabolic pathways potentially associated with anthocyanin biosynthesis. Conclusions This study provides novel insights into the biochemical mechanisms underlying peanut resistance to A. flavus, while also supporting the valorization of peanut by-products and the breeding of resistant cultivars.